Diversidade parasitária em vertebrados do Parque Natural das Lagoas de Cufada (GUINÉ-BISSAU) - Rosa, Fernanda; Crespo, Maria Virgínia (2004)
Apresentação em Painel The importance of the parasitological fauna diversity and its spacial distribution and temporal evolution in different ecossystems, as well as its influence on their vertebrate hosts has increased in the last decades, especially when protection and conservation of ecossystems, sustainable use of natural resources and protection of local residents health are involved. During a biodiversity study in the Natural Park of the Lagoons of Cufada (Guinea-Bissau, West Africa), a parasitological survey in domestic (Canis vulgaris and Bos taurus) and in wild animals (PRIMATES: Cercopithecus mona campbelli, Chlorocebus aethiops sabaeus, Papio cynocephalus papio and Procolobus badius temminckii; RODENTIA: Arvincanthis niloticus, Rattus rattus and Praomys (Mastomys) sp.; CHELONIA: Kinixys belliana nogueyi) was performed. The helminths were collected after a decanting process and preserved in alcohol 70º. The morphological studies were performed in specimens clarified by lactofenol (NEMATODA) and stained by chloridrical alcoholic carmin (PLATYHELMINTHES). The ticks (ARTHROPODA, Ixodoidea) were collected directly from skin. Up till now the specimens identified were included in PLATYHELMINTHES (TREMATODA - Dicrocoelium hospes, Watsonius watsoni - and CESTODA - Bertiella studeri and Hymenolepis diminuta), NEMATODA (ENOPLIDA - Trichuris trichuria; SRONGYLIDA - Strongyloides fuelleborni, Ternidens deminuta, Oesophagostomum bifurcum, O. stephanostomum, Oesophagostomum sp., Globocephalus longemucronatus, Pithecostrongylus sp., Hyostrongylus rubidus; ASCARIDIDA - Subulura distans; RHABDITIDA – Enterobius sp. and SPIRURIDA), PENTASTOMIDA (Armillifer armillatus) and ARTHROPODA (INSECTA - DIPTERA, BRACHYCERA; IXODOIDEA - Ambyomma spp.; Hyalomma sp.; Boophilus sp. and Rhipicephalus sp.) were identified. The continuity of this parasitological study is stressed out by the contribute to local diversity fauna knowledge and by the intertransmissibility of some species between domestic and wild vertebrates. On the other ...